CENTER OF MASS (CENTROID) ANALYSIS ON ATV (ALL TERRAIN VEHICLE) TYPE ROKETS WIMCYCLE 110 CC - Panca Suwanda, Aggy; Rachmat, Asep; Koswara, Engkos (Universitas Majalengka, 2021)
In an ATV (All Terrain Vehicle) vehicle, the center of gravity is the point at which the vehicle will be in equilibrium. When the vehicle experiences translational and rotational motion at the same time, then at that time The center of gravity will act as the axis of rotation and the trajectory of motion, from the center of gravity This describes the trajectory of the translational motion. The center of gravity is a point of perfect balance or a center distribution of weight. At this point the gravitational force acts, for objects that are have any shape location center of gravity is searched by calculations, calculations are based on the assumption that we can take some points of the object you want to calculate the center of gravity multiplied by the weight at each point then add up and divide by the total weight at each point. It is said that the center of gravity is also the center of mass near the earth's surface, but for a certain height above the earth center of gravity and center of gravity must be distinguished. The distance from the center of mass when viewed from the side view is 0.42 m from the front axle and 0.48 m from the rear axle. The center of mass distance from the rear view is 0.35 m from the right wheel axis and 0.35 m from the left wheel. The height of the center of mass from the axis of the wheel axle is 0,39 m.